Stable Isotope Dilution Analysis of the Major Prenylated Flavonoids Found in Beer, Hop Tea, and Hops - Buckett, Lance; Schinko, Simone; Urmann, Corinna; Riepl, Herbert; Rychlik, Michael (Frontiers in Nutrition, 2020)
Prenylated flavonoids from hops (Humulus lupulus) have become of interest in recent years due to a range of bioactivities. The potential health benefits of prenylated flavonoids include anti-cancerous activities and treatment of the metabolic syndrome among others. Since prenylated flavonoids from hops have shown pharmaceutical potential in clinical trials, robust analytical methods to determine their concentrations in food, supplements and beverages are required. One such, the gold standard of analytical methods, is stable isotope dilution analysis due to its ability to compensate matrix effects and losses during sample work-up. As no commercial standards were available, the synthesis of seven different prenylated flavonoid isotopes utilizing various strategies (microwave assistance, acid base catalyst in the presence of deuterated substance and lastly, the use of Strykers catalyst) is described. The produced prenylated flavonoid isotopes were then applied in the first stable isotope dilution analysis method that quantified six natural prenylated flavonoids (Isoxanthohumol, Isoxanthohumol-C, 8 Prenylnaringenin, 6- Prenylnaringenin, Xanthohumol and Xanthohumol-C) in beer, hops and hop tea. The SIDA-LC-MS/MS method was validated resulting in LODs and LOQs for all analytes between 0.04 to 3.2 µg/L. Moreover, due to the simple clean-up the developed method allows the prospect for measuring clinical samples in the future.